THE EFFECT OF DUTCH DISEASE VS NEW PARADIGM OF TOURISM DEVELOPMENT: Case Study of Changes in Bali's Economic Structure - Luh Gede , Meydianawathi; Agus , Suman (Eksis: Jurnal Riset Ekonomi dan Bisnis, 2023)
This article aims to explain the possible effects of Dutch Disease (DD) on tourism development in Bali and how the new paradigm of tourism development can counter the DD effect. As is known, the development of this sector has made tourism a leading industry for Bali's economic growth. However, this condition in the long term is a sign that Bali is starting to experience a significant DD effect, where growth in critical sectors hampers growth in other industries and may even slow down the overall growth rate of the regional economy. Using descriptive analysis techniques, this article utilizes data sharing on agricultural sector growth and labour profile by sector in the Province of Bali to describe how the possible effects of the Dutch disease on the Bali economy occurred.